A CRITICAL STUDY ON USE OF RUBRICS IN TECHNICAL INSTITUTIONS OF INDIA - Gupta, Badrilal; Bundela Gupta, Pratibha (Pusat Asesmen dan Pembelajaran, 2021)
The implementation of outcome-based education in technical institutions compelled the teachers to use outcome-based assessment tools and techniques to assess the learning of the students with reference to defined learning outcomes. Rubrics are valid, reliable, and accurate assessment tools that are being used by trained and not trained teachers in the assessment. This study was conducted to critically examine the use of rubrics in technical institutes. The paper is based on primary data gathered from 315 technical teachers from July 2020 to November 2020 using researchers designed Google Form. The findings of the study are noted on the training of teachers in preparation and use of rubrics, the purpose of using rubrics, abilities assessed using rubrics, types of rubrics prepared and used, the process of preparing rubrics, major difficulties, and barriers to use of rubrics, the process of ensuring validity and reliability of using rubrics, the impact of using rubrics, the decision was taken based on the analysis of results of rubrics and suggestions to improve the quality and use of rubrics at institute level. Researchers have concluded and noted suggestions for harnessing the full potential of rubrics. Areas for further study are stated.